Patterns of Antecedents of Catastrophic Reactions in Nursing Home Residents With Dementia in the United States - Hye-A Yeom, PhD, R; Nancy M. Watson, PhD, RN, FGSA (Elsevier, 2009)
The purpose of this study was to describe the patterns of antecedents of catastrophic reactions (CRs) in nursing home residents with dementia in the United States. Methods: A total of 229 catastrophic reaction events were the sample for this study. Ten antecedent variables were selected and analyzed using cluster analysis to address the patterns of antecedents of CRs in dementia. Data were obtained from field observation and a structured recording form over a 6-week period covering all 7 days of the week and all three shifts (i.e., 21 shifts in total) in two nursing homes in the United States. Results: This study showed that there were two distinct patterns of antecedent conditions at the time of, or immediately prior to, CRs in dementia: (a) a cluster of antecedents that consists of components of the physical environment including public location, olfactory stimulation, use of media, sundowning hours, and being in a dementia unit ("Stimulation in Early Evening"); and (b) a cluster of antecedents that is composed of mixed components of the physical and social environment including olfactory stimulation, activities of daily living (ADL)-related care activities, demands of tasks, and being in a dementia unit ("Stress due to Care, Tasks, and Odors"). Conclusion: The findings suggest that elders who are exposed to overstimulation in sundowning hours or experience stress from care activities and task performance beyond their baseline competency are likely to be at risk of presenting with CRs. Health care providers need to be aware that a CR is a multi-factorial phenomenon in which multiple contextual antecedents are involved and that creation of a therapeutic physical and social milieu is an important nursing goal in preventing the occurrence of CRs in nursing home residents with dementia. [Asian Nursing Research 2009;3(3):99-110]